2021
DOI: 10.1038/s41467-021-23963-7
|View full text |Cite
|
Sign up to set email alerts
|

Vortex states in an acoustic Weyl crystal with a topological lattice defect

Abstract: Crystalline materials can host topological lattice defects that are robust against local deformations, and such defects can interact in interesting ways with the topological features of the underlying band structure. We design and implement a three dimensional acoustic Weyl metamaterial hosting robust modes bound to a one-dimensional topological lattice defect. The modes are related to topological features of the bulk bands, and carry nonzero orbital angular momentum locked to the direction of propagation. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 73 publications
0
18
0
Order By: Relevance
“…Furthermore, multifunctional vortex beams of sound can also be obtained by changing phase profiles, such as focusing vortices [38,39] and vortex beams with asymmetric propagation [40], which have potential special applications. Additionally, the finite element method based on the COMSOL Multiphysics software has been introduced to numerically design and optimize different types of acoustic vortex devices, such as unidirectional vortex beams through acoustic Weyl crystal with a topological lattice defect, and a vortex converter composed of an acoustic metagrating in a waveguide [10,37,40], and the corresponding simulated results agree well with the measured ones. However, these aforementioned vortex beams are generally observed on structure surfaces or in waveguides with a hard boundary owing to the characteristic of easy diffusion in free space.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Furthermore, multifunctional vortex beams of sound can also be obtained by changing phase profiles, such as focusing vortices [38,39] and vortex beams with asymmetric propagation [40], which have potential special applications. Additionally, the finite element method based on the COMSOL Multiphysics software has been introduced to numerically design and optimize different types of acoustic vortex devices, such as unidirectional vortex beams through acoustic Weyl crystal with a topological lattice defect, and a vortex converter composed of an acoustic metagrating in a waveguide [10,37,40], and the corresponding simulated results agree well with the measured ones. However, these aforementioned vortex beams are generally observed on structure surfaces or in waveguides with a hard boundary owing to the characteristic of easy diffusion in free space.…”
Section: Introductionmentioning
confidence: 71%
“…Recent years have witnessed the great development of acoustic vortex beams owing to their extensive applications in a wide range of fields, such as sound communication [1,2] and particle trapping [3][4][5]. The acoustic vortex beam can transfer different-order vortex wavefronts with orbital angular momentum, opening up a new degree of freedom for sound modulations [6][7][8][9][10]. Traditionally, by designing active sound arrays composed of phased sources [2,[11][12][13], researchers have experimentally realized acoustic vortex beams to manipulate micro-particles underwater.…”
Section: Introductionmentioning
confidence: 99%
“…Two years after this theoretical work, Weyl points were experimentally observed in the microwave frequency range [8]. Following this first experimental demonstration, the realization of Weyl points has been achieved using photonic crystals [9,10,43,44,[55][56][57][58][59][60], phononic crystals [3,14,[61][62][63][64][65][66], metals [67][68][69][70] and semimetals [71][72][73][74][75][76][77].…”
Section: Band Degeneraciesmentioning
confidence: 97%
“…Topological lattice defects [27] have been extensively studied in electronic systems [138][139][140] and classical systems [141][142][143][144][145][146][147][148] over the past decade. The classification of topological lattice defects depends on the holonomy along a closed path around the defect core [25,149].…”
Section: Topological Defect Statesmentioning
confidence: 99%
“…The dislocations and disclinations are defined as a gauge flux for translational symmetry and rotational symmetry, respectively [28]. Dislocations and disclinations are mainly investigated on honeycomb lattices and square lattices [149], and it has been demonstrated that they can serve as a bulk probe to detect the topological nature which exhibits topological states [139][140][141][142][143][146][147][148][154][155][156] and/or fractional charges [144,145,157,158] in TCIs protected by crystal symmetries. More recently, topological defect states have been proposed in elastic materials [87,[159][160][161], and then we will discuss the related papers.…”
Section: Topological Defect Statesmentioning
confidence: 99%